37 Medication exchange and sharing network program (MESNP) initiative to cope with drug shortages in the kingdom of saudi arabia (KSA). (25th October 2019) - AlAzmi, Aeshah; AlRashidi, Rph Faris
Abstract : Background: Drug shortages are a major public health concern and remain a persistent problem worldwide. Saudi Arabia is one of the richest and fastest growing countries in the Middle East. Despite that, Saudi Arabian drug markets are not immune to drug shortages. Although exact figures about drug shortages in Middle Eastern countries in general and in Saudi Arabia, in particular, are lacking, there is an emerging yet still limited number of reports about the drug shortage. It is, however, a fact that the drug shortages are affecting the Middle East in general and the Kingdom of Saudi Arabia (KSA) in particular. At the time we conducted this project, the Saudi Food and Drug Administration (SFDA) had not yet fully activated and implemented its role in tracking drug shortages and the role of other regulatory bodies were either outdated or unknown. Healthcare is one of the main focus areas of Saudi Vision 2030, which represents a comprehensive plan for the entire economic structure of Saudi Arabia. In order to ensure the Saudi Vision 2030 becomes reality, we should focus on more efficient use of our current resources. Based on that, we identified an innovative solution at the national level to collaborate and cope with the current situation by developing a centralized Medication Exchange and Sharing Network Program (MESNP). Methods: A quality improvement process map method was used for this project. Baseline evaluation included a review of possible reasons and strategies to manage medication shortages, recognize potential associated safety issues, and we developed MESNP as a national novel project to cope with medication shortages using a telegram as the preferred social media platform for group creation and communication. Results: A total of 500 reports were received. The majority of reports (70%) were raised by the Ministry of Health (MOH). A number of reports constituted requests for drug supplies due to shortages (n=315) and reports indicating the availability of overstock items for redistribution (n=185). Almost 98% of overstocking drug reports were redistributed, which covered 75% of drug shortage requests. Conclusion: We believe that this is the first national novel project aiming to address drug shortages. The optimistic findings of this project were the proactive identification of data and development of a framework to collect data about national drug shortages to facilitate the medication exchange and sharing between organizations to prevent drug wastages and shortages for better patient care.